HTS : a hierarchical method for load balancing in autonomous networks. - Ahmad Zukarnain, Zuriati; Udzir, Nur Izura; Othman, Mohamed (IJCSNS (International Journal of Computer Science and Network Security), 2008)
The load balancing is the most important issues to reduce congestion in autonomous computer networks. The inter-domain traffic control methods have been addressed by researchers. In this paper, the authors are proposed HTS; a BGP-based hierarchical network traffic reconfiguration method to redistribute traffic on overloaded link for IP-based network. Proposed algorithm fulfills at two steps. Firstly overload detection function through an explorer algorithm to construct overloaded link table due to disruption link. Finally HTS scheme scattering traffic on overloaded path to exterior level. The performed experiments have been shown efficiency of proposed method in load balancing and good performance when the offered traffic loads change randomly.